Transversalidade nas ações da Educação Especial: a realidade dos Institutos Federais de Educação, Ciência e Tecnologia do Rio Grande do Sul - Welker, Gisiele Michele (2016)
The theme of inclusion is considered current, it is in constant improvement and it is extremely important to the educational context of the Special Education target audience. This study approaches the Master's Thesis on the theme - Transversality in the actions of the Special Education: the reality of the Federal Institutes of Education, Science and Technology of Rio Grande do Sul Brazil. The study has as general objective to know which are the transversalities and actions of Special Education in these Institutes. The methodological path corresponded to the application of a questionnaire by means the Google drive tool, a virtual service from Google that allows storage and file synchronization, via online, directed to the coordinators who work with inclusive actions of the Federal Institutes (FIs) investigated. The research was descriptive exploratory in data collection step and analytical qualitative in discussion of the results step. The data were analyzed from the theory of Content Analysis and revealed an initiated work in the field of inclusion which is being gradually carried out. Some campi are already accessible, but there is still a lack of professionals in the field. In addition, awareness and discussion among education professionals need to be effected continuously, allowing the expansion and development of educational transversalities that will serve as a framework of inclusion in FIs. It concludes that the transversalities, identified as practical relations in the educational routine in FIs, are at an early stage. The technical and scientific knowledge of education professionals on the inclusion area is determining the continuity of inclusive features actions, collaborating not only the necessary transversalities, but essentially and consequently on inclusion, learning and attendance of the target audience students of Special Education.